Anaemia in Pregnancy - Rahma, Fathin Auliya (Jurnal Ilmiah STIKES Yarsi Mataram, 2023)
Background: Anaemia is a condition that describes a person's haemoglobin/hematocrit levels which fall ± two standard deviations below the normal average for individuals of the same age, sex, and height. In developing countries, there are many factors contributing to anaemia during pregnancy. A woman with anaemia during pregnancy is at a greater risk of having a premature baby and giving birth to a baby with a low birth weight (LBW). Most neonatal deaths in developing countries occur due to premature births and low birth weights. Methods: This literature review reviews various articles discussing anaemia and pregnant women, both from national and international scientific literature within the last 10 years of publication. Results: This literature review includes six pieces of literature published within the past ten years. In this review, three articles specifically discuss the management of anaemia during pregnancy. Conclusion: Anaemia is a condition that describes a person's haemoglobin/hematocrit levels which fall ± two standard deviations below the normal average for individuals of the same age, sex, and height. The causes of anaemia during pregnancy in developing countries have many contributing factors. Aanemia during pregnancy is reported to have a negative impact on the health of mothers and children. Anaemia in pregnant women has a relatively high mortality rate if not treated immediately, which makes it necessary to know the best and most efficient way to manage them.